2022
DOI: 10.3390/ijms23052713
|View full text |Cite
|
Sign up to set email alerts
|

Bone Fragility in Gastrointestinal Disorders

Abstract: Osteoporosis is a common systemic disease of the skeleton, characterized by compromised bone mass and strength, consequently leading to an increased risk of fragility fractures. In women, the disease mainly occurs due to the menopausal fall in estrogen levels, leading to an imbalance between bone resorption and bone formation and, consequently, to bone loss and bone fragility. Moreover, osteoporosis may affect men and may occur as a sequela to different diseases or even to their treatments. Despite their wide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 210 publications
(280 reference statements)
0
7
0
2
Order By: Relevance
“…It is well known that gastrointestinal diseases, like inflammatory bowel disease (IBD), celiac disease, gastric bypass surgery, and hepatic diseases lead to secondary osteoporosis . 45 47 It is very important to recognize secondary osteoporosis since the treatment of these patients may be different; moreover, their therapeutic response may vary, if the underlying disease is not recognized and not treated. According to the article of Mirza et al , 48 “up to 30% of postmenopausal women and 50 to 80% of men are found to have factors contributing to osteoporosis.” Factors contributing to secondary osteoporosis in gastrointestinal diseases include malabsorption, malnutrition, and/or detrimental drug therapy.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that gastrointestinal diseases, like inflammatory bowel disease (IBD), celiac disease, gastric bypass surgery, and hepatic diseases lead to secondary osteoporosis . 45 47 It is very important to recognize secondary osteoporosis since the treatment of these patients may be different; moreover, their therapeutic response may vary, if the underlying disease is not recognized and not treated. According to the article of Mirza et al , 48 “up to 30% of postmenopausal women and 50 to 80% of men are found to have factors contributing to osteoporosis.” Factors contributing to secondary osteoporosis in gastrointestinal diseases include malabsorption, malnutrition, and/or detrimental drug therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoporosis is a common systemic disease or skeletal disorder (10,11). Worldwide, osteoporosis causes millions fracture annually, resulting in an Osteoporotic/fragility fracture (12,13).…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 11 Intestinal inflammation, production of pro-inflammatory cytokines, and the presence of neutralising antibodies against osteoprotogerin (OPG) enhance bone absorption, contributing to the decreased BMD that is noted in these patients. 12 , 13 One study exhibited a higher percentage of anti-OPG antibodies in CD patients (10%), compared to the general population. 14 It has been also reported that OPG/RANKL ratio is lower in CD patients, compared to controls, and is positively correlated with spine BMD.…”
Section: Literature Reviewmentioning
confidence: 99%